Impact of an education intervention using email for the prevention of weight gain among adult workers. Issue 7 (20th August 2013) - Jaime, Patricia Constante; Bandoni, Daniel Henrique; Sarno, Flávio
Abstract Objective To evaluate the impact of a worksite intervention to prevent weight gain among adult workers. Design A controlled community trial was performed by dividing the workers into two groups: intervention group (IG) and control group (CG). The theoretical framework applied was Intervention Mapping Protocol and the intervention was implemented through interactive software for weight self-monitoring. To evaluate the impact of the intervention, the differences in weight, BMI and waist circumference between the IG and CG were assessed before and 6 months after the intervention by regression models. Additionally, the sustainability of the intervention was evaluated at 12 months after the intervention. Settings São Paulo, Brazil. Subjects Four companies; 281 workers for the analysis of effectiveness and 427 for the analysis of sustainability. Results The intervention resulted in significant reductions in weight, BMI and waist circumference in the IG compared with the CG. The impact of the intervention on IG individuals' body weight was −0·73 kg, while the weight of CG individuals increased. IG individuals with adequate initial weights did not show significant variations, while those who were overweight demonstrated a significant reduction in body weight. The intervention resulted in a reduction of 0·26 kg/m2 in BMI and 0·99 cm in waist circumference, and the sustainability analysis after 12 months showed a continued reduction in body weight (−0·72 kg). Conclusions The behavioural intervention was effective, resulting in weight maintenance among participants with adequate initial weight and in significant reductions among those who were overweight. More research on longer-term weight maintenance is needed.